Neutrosophic Crisp Set & Relations - A. A. Salama (Neutrosophic Sets and Systems, 2014)
In a world full of indeterminacy, traditional crisp set with its boundaries of truth and false has not infused itself with the ability of reflecting the reality. Therefore, neutrosophic found its place into contemporary research as an alternative representation of the real world. In this paper, we aim to develop a new type of neutrosophic crisp sets called the *-Neutrosophic crisp sets as a generaliza tion of the star intuitionistic set introduced by Indira et al.[4] , and hence studying some of its properties . To this end we will investigate the notion of *-Neutrosophic relation and some of its properties.